2023
DOI: 10.1371/journal.pone.0294763
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K2 (MK-7) attenuates LPS-induced acute lung injury via inhibiting inflammation, apoptosis, and ferroptosis

Yulian Wang,
Weidong Yang,
Lulu Liu
et al.

Abstract: Acute lung injury (ALI) is a life-threatening disease that has received considerable critical attention in the field of intensive care. This study aimed to explore the role and mechanism of vitamin K2 (VK2) in ALI. Intraperitoneal injection of 7 mg/kg LPS was used to induce ALI in mice, and VK2 injection was intragastrically administered with the dose of 0.2 and 15 mg/kg. We found that VK2 improved the pulmonary pathology, reduced myeloperoxidase (MPO) activity and levels of TNF-α and IL-6, and boosted the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Recent animal research has demonstrated that vitamin K2 is a potential therapeutic option for acute lung injury. It may alleviate acute lung injury by regulating inflammation, apoptosis, ferroptosis, and elastin degradation [ 98 ]. This may be due to the longer half-life of vitamin K2 [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent animal research has demonstrated that vitamin K2 is a potential therapeutic option for acute lung injury. It may alleviate acute lung injury by regulating inflammation, apoptosis, ferroptosis, and elastin degradation [ 98 ]. This may be due to the longer half-life of vitamin K2 [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study [ 63 ], we also carried out some protective studies of vitamin K2 on acute lung injury. The conclusions of the two articles are consistent, both of which reflected the fact that vitamin K2 can protect ALI mice by interfering with inflammation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6 male mice were fed in an animal house with a constant temperature of 23 ± 2 °C, humidity of 60–75% and alternating light and dark per 12 h. Based on our previous studies 20 and preliminary experiments, we determined the dose of VK2 intervention in this experiment. After one week of adaptive feeding, a total of 42 mice were randomly divided into seven groups (n = 6): control group (C), control + vitamin K2 (0.1 mg/kg, 0.2 mg/kg and 0.4 mg/kg) group (C + VK2), high fat diet group (HFD), high fat diet + 0.1 mg/kg vitamin K2 group [HFD + VK2(L)], high fat diet + 0.2 mg/kg vitamin K2 group [HFD + VK2(M)], high fat diet + 0.4 mg/kg vitamin K2 [HFD + VK2(H)] group and high fat diet + vehicle group (HFD + V).…”
Section: Methodsmentioning
confidence: 99%